Metal-free N-doped carbon nanofibers as an efficient catalyst for oxygen reduction reactions in alkaline and acid media. (21st November 2016) - Li, Ruchun; Shao, Xiaofeng; Li, Shuoshuo; Cheng, Pengpeng; Hu, Zhaoxia; Yuan, Dingsheng
Abstract: The development of metal-free catalysts to replace the use of Pt has played an important role in relation to its application to fuel cells. We report N-doped carbon nanofibers as the catalyst of an oxygen reduction reaction, which were synthesized via carbonizing bacterial cellulose-polypyrrole composites. The as-prepared material exhibited remarkable catalytic activity toward the oxygen reduction reaction with comparable onset potential and the ability to limit the current density of commercial Pt/C catalysts in both alkaline and acid media due to the unique porous three-dimensional network structure and the doped nitrogen atoms. The effect of N functionalities on catalytic behavior was systematically investigated. The results demonstrated that pyridinic-N was the dominating factor for catalytic performance toward the oxygen reduction reaction. Additionally, N-doped carbon nanofibers also demonstrated excellent cycling stability (93.2% and 89.4% retention of current density after chronoamperometry 20 000 s in alkaline and media, respectively), obviously superior to Pt/C.